The Benefits of Equine-Assisted Services for Autistic Children: An Exploration of Effectiveness and Mechanisms of Change - Fischer von Edelau, Nina (Curtin University, 2024)
This project investigates the effectiveness and mechanisms of equine-assisted services (EAS) for autistic children through three studies employing meta-analytical, quantitative, and qualitative methodologies. Findings indicate EAS' potential to enhance emotional and social outcomes, contributing to a more rigorous evidence base and emphasising the importance of integrating direct insights from autistic individuals when tailoring interventions. The work lays the foundation for future EAS research that is evidence-informed, theory-driven and supports neurodiversity-affirming practice.